Characteristics of Procurement Methods in Malaysia – Comparing Design-Bid-Build, Design-Build and Construction Management - Suratkon, Azeanita; Yunus, Riduan; Deraman, Rafikullah (International Journal of Sustainable Construction Engineering and Technology, 2020)
Design-Bid-Build (DBB) or commonly known as Traditional method is the earliest and most prevalent procurement method used in Malaysian construction industry. Design-Build (DB) and Construction Management (CM) procurement methods were later introduced in Malaysia as an endeavour to satisfy and accommodate the increase in project complexity and the need for avoiding drawbacks of the Traditional methods. Each procurement method has different nature and possesses certain characteristics. Therefore, this study was carried out to ascertain and compare the characteristics of these three procurement methods that are implemented in building construction projects in Malaysia. A questionnaire survey was conducted among architects, consultants, contractors and owners or developers to elicit their feedback on the characteristics which were categorised into time, cost, quality, complexity and flexibility, degree of involvement and responsibility allocation and technical expertise. The findings indicated that only DB method almost fulfils all the characteristics under the six categories, whereas, DBB methods garnered agreement only for certain characteristics under time, cost, complexity and flexibility and technical expertise categories. Meanwhile, the only CM method’s characteristics that satisfy agreement from the respondents are the often used of fast track approach and lack of certainty in price. This study concludes that when a procurement method is adopted for a construction project, not all the features or characteristics will turn out as expected. There are many factors that contribute and are influential on the success in procurement methods that are worth for further investigation.